Proximal Fusion Level Above First Coronal Reverse Vertebrae: An Essential Factor Decreasing the Risk of Adjacent Segment Degeneration in Degenerative Lumbar Scoliosis. Issue 1 (January 2023) - Wang, Hui; Sun, Zhuoran; Wang, Longjie; Zou, Da; Li, Weishi
Study Design: Retrospective radiological analysis. Objective: To explore whether proximal fusion level above first coronal reverse vertebrae (FCRV) could decrease risk of adjacent segment degeneration (ASD) in degenerative lumbar scoliosis (DLS). Methods: One hundred and 16 DLS patients were divided into 2 groups according to occurrence of ASD: study group (ASD positive group) and control group (ASD negative group). FCRV was defined as the first vertebrae that presents opposite orientation of asymmetric Hounsfield unit (HU) ratio from the other vertebrae within major curve. Incidence of ASD was evaluated in subgroups according to location between FCRV and upper instrumented vertebrae (UIV). Results: The fusion level was shorter in study group than that in control group. There were 12 patients presented FCRV 2-level proximal than SV, 32 patients presented FCRV 1-level proximal than SV, 35 patients presented the same vertebra of FCRV with SV, 23 patients presented FCRV 1-level distal than SV, 14 patients presented FCRV 2-level distal than SV. When UIV located above FCRV, no patient presented ASD, while 15.4% patients presented ASD when UIV located on FCRV. In study group, proximal scoliosis progression was detected in 1 patient (3.9%) when UIV located on FCRV, and 17 patients (29.8%) when UIV located below FCRV. Conclusions: Proximal fusion level above FCRV could decrease the risk of ASD in DLS, especially for the proximal scoliosis progression. FCRV represent the transitional point of the mechanical load on coronal plane, and may be within a more stable condition than stable vertebrae measured from radiographs.